2018
DOI: 10.1016/j.synbio.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Simple glycolipids of microbes: Chemistry, biological activity and metabolic engineering

Abstract: Glycosylated lipids (GLs) are added-value lipid derivatives of great potential. Besides their interesting surface activities that qualify many of them to act as excellent ecological detergents, they have diverse biological activities with promising biomedical and cosmeceutical applications. Glycolipids, especially those of microbial origin, have interesting antimicrobial, anticancer, antiparasitic as well as immunomodulatory activities. Nonetheless, GLs are hardly accessing the market because of their high cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 258 publications
(238 reference statements)
2
20
0
2
Order By: Relevance
“…Indeed, all the PPTases from several filamentous fungi and some yeasts contain the same conserved regions as the PPTase obtained in this study [35][36][37]. In facts, it has been well documented that fatty acid synthases (FASs), PKSs, nonribosomal peptide synthetases (NRPSs) and the key enzyme for lysine biosynthesis are also activated by the PPTase [13,34]. Therefore, the HR-PKS obtained in this study must be activated by the PPTase (Figure 4).…”
Section: Analysis Of the Fatty Acid Compositions In The Extracellularsupporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, all the PPTases from several filamentous fungi and some yeasts contain the same conserved regions as the PPTase obtained in this study [35][36][37]. In facts, it has been well documented that fatty acid synthases (FASs), PKSs, nonribosomal peptide synthetases (NRPSs) and the key enzyme for lysine biosynthesis are also activated by the PPTase [13,34]. Therefore, the HR-PKS obtained in this study must be activated by the PPTase (Figure 4).…”
Section: Analysis Of the Fatty Acid Compositions In The Extracellularsupporting
confidence: 57%
“…The data were obtained using the HPLC-MS. domain of the HR-PKS, either (Figure 7). However, it has been reported that an activated acyl donor, mostly acyl-CoA or -ACP can be transferred to a glycosyl acceptor by making an ester bond between the hydroxyl group (nucleophile) of the acceptor and the acyl donor's carbonyl group during glycolipid biosynthesis [34]. We reasoned that the Est1 could also catalyze such a reaction as shown in Figure 8.…”
Section: Analysis Of the Fatty Acid Compositions In The Extracellularmentioning
confidence: 97%
“…Перспективи широкого застосування поверхнево-активних речовин природного походження (біоПАР, біосурфактанти) обумовлені їх цінними фізико-хімічними властивостями (зниження поверхневого натягу розчинів, емульгування, солюбілізація гідрофобних сполук, піноутворення, змочування поверхонь), які поєднуються з біодеградабельністю і низькою токсичністю цих речовин [1,2]. Серед екологічно безпечних ПАР найперспективнішими є продукти мікробного синтезу, перевагами яких є висока ефективність, стійкість у широкому діа-пазоні значень температури, рН, концентрацій солей, біологічна активність (вплив на метаболізм мікроорганізмів, проникність клітинних мембран, активність ферментів тощо), використання відновлюваної сировини для їх отримання [3]. При розробці технологій одержання біоПАР актуальною проблемою є пошук активних штамів-продуцентів та оптимізація їх біосинтезу.…”
Section: вступunclassified
“…Trends in healthy eating and growing progress in research into functional natural food additives have been noted, including those that exhibit antioxidant activity without side effects compared to synthetic compounds (Abdel-Mawgoud & Stephanopoulos, 2018;Bandyopadhyay, Chakraborty & Bhattacharyya, 2014). Thus, in order to reduce the use of synthetic emulsifiers or constituents of low nutritional value in foods, the use of biosurfactants has aroused industrial interest (Campos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%